2019
DOI: 10.1007/s42452-019-1856-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of foamed concrete reinforced with hybrid fibers and exposed to elevated temperatures

Abstract: This paper demonstrates the behavior of foamed concrete reinforced with either or both carbon fibers and polypropylene fibers exposed to elevated temperatures. Various volumetric fractions of carbon fibers (0.5, 1 and 1.5%) were used to reinforce foamed concrete mix. Also, hybrid fibers of carbon fibers (CF) and polypropylene fibers (PPF) as 1%CF + 0.5% PPF and 0.5%CF + 1%PPF were prepared. Lastly, the mono polypropylene fibers as 1.5% PPF were used to reinforce the foamed concrete mix. These different mixes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Thereafter, Dawood E.T. et al [21] further demonstrated the effects of hybrid carbon fibers and polypropylene fibers on improving the mechanical properties of the foamed concrete under different temperature. In general, with the temperature increasing, the mechanical properties will decrease, compared with the carbon fiber reinforce foamed concrete, the polypropylene reinforced foamed concrete is more sensitive to the elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Dawood E.T. et al [21] further demonstrated the effects of hybrid carbon fibers and polypropylene fibers on improving the mechanical properties of the foamed concrete under different temperature. In general, with the temperature increasing, the mechanical properties will decrease, compared with the carbon fiber reinforce foamed concrete, the polypropylene reinforced foamed concrete is more sensitive to the elevated temperature.…”
Section: Introductionmentioning
confidence: 99%